Pelayanan Transportasi Laut Di Pelabuhan Alai Insit-Pecah Buyung Kabupaten Kepulauan Meranti - Hasrizal, Hasrizal; Sujianto, Sujianto; Mayarni, Mayarni (Peneliti.net, 2024)
The large number of fishing activities around the crossing route is a complaint from ship captains. Shipping lanes should be free from fishing activities in any form, whether it be Gumbang, Rawai and other activities that could disrupt shipping activities. Apart from damaging ships, this activity can also harm fishermen, for example material losses such as damaged fishing gear. If the net is wrapped around the propeller, the engine will heat up and cause damage. Diving will definitely not be possible because of the murky water conditions. In reality, fishing activities disrupt the operation of this transportation, but we need to realize that fishing activities existed long before the operation of the Insit-Pecah Buyung port, Meranti Islands Regency. The research results show that the quality of public services at the Alai Insit-Pecah Buyung Meranti Islands crossing port at this time, in the research, chose to use 5 dimensions of public service quality including: a. Tangible dimensions, paying attention to the appearance of the officers, the comfort of the place where the service is carried out also affect the location of the Insit-Pecah Buyung port, which is not good and hot, making visitors uncomfortable. b. The reliability dimension, many customers do not know about this SPM and the ability and expertise of officers in operating service aids at the Alai Insit-Pecah Buyung crossing port. So far there have been no visible problems from the inability of employees to operate the technology. c. Responsiveness dimension, officers at the port carry out services quickly, precisely and carefully but the service on certain days is not yet effective. All customer complaints are responded to by officers. For customer complaints, we provide a box that is used to enter criticism, complaints or suggestions. d. Assurance dimension, the officer provides a guarantee of cost certainty, a guarantee of legality in the service. e. The empathy dimension, the service system at the Alai Insit-Pecah Buyung Meranti Islands crossing port does not yet use a number system for every customer who requests service so that there is no discrimination. Meanwhile, the overall supporting and inhibiting factors show good things with the supporting factors involving officers with various services that can be provided to customers with the officers' expertise in doing everything needed at the port, almost all dimensions of this transportation service are carried out professionally and competent. The obstacles that occur do not have a big influence on this service system, some deficiencies occur due to certain factors such as weather, or the productivity of passengers or vehicles is different every day.